Mountain Mandalas: Shugendō in Kyūshū, by Allan G. Grapard. (27th August 2019) - Sala, Emanuela
Abstract : Mountain Mandalas: Shugendō in Kyūshū, by Allan G. Grapard. Bloomsbury. 2016. 320 pp. Hb. £90. ISBN–13: 9781474249003. Pb. £31. ISBN-13: 9781350044937. Ebook £34.54. ISBN-13: 9781474249027.